Targeting Lipoprotein(a): Can RNA Therapeutics Provide the Next Step in the Prevention of Cardiovascular Disease? - Thau, Henriette; Neuber, Sebastian; Emmert, Maximilian Y.; Nazari-Shafti, Timo Z. (Cardiology and Therapy, 2024)
Numerous genetic and epidemiologic studies have demonstrated an association between elevated levels of lipoprotein(a) (Lp[a]) and cardiovascular disease. As a result, lowering Lp(a) levels is widely recognized as a promising strategy for reducing the risk of new-onset coronary heart disease, stroke, and heart failure. Lp(a) consists of a low-density lipoprotein-like particle with covalently linked apolipoprotein A (apo[a]) and apolipoprotein B-100, which explains its pro-thrombotic, pro-inflammatory, and pro-atherogenic properties. Lp(a) serum concentrations are genetically determined by the apo(a) isoform, with shorter isoforms having a higher rate of particle synthesis. To date, there are no approved pharmacological therapies that effectively reduce Lp(a) levels. Promising treatment approaches targeting apo(a) expression include RNA-based drugs such as pelacarsen, olpasiran, SLN360, and lepodisiran, which are currently in clinical trials. In this comprehensive review, we provide a detailed overview of RNA-based therapeutic approaches and discuss the recent advances and challenges of RNA therapeutics specifically designed to reduce Lp(a) levels and thus the risk of cardiovascular disease.